CHILDREN'S RIGHTS IN WORSHIP AND MORALITY EDUCATION: An Islamic Perspective on the Role of Parents - Muzekki, Muzekki; Hijriyah, Umi; Irfani, Bambang; Zulkifli, Zulkifli; Erlina, Erlina (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2024)
Child education in Islam encompasses various aspects, including worship and moral education. Parents play a pivotal role in shaping children's character, instilling noble morals, and introducing the values of worship from an early age. This study aims to examine children's rights to receive worship and moral education from an Islamic perspective and to analyse the role of parents in fulfilling these rights. Using a literature review method, this study explores parental obligations according to Islamic teachings, ranging from the education of tawhid and worship to the development of ethics and noble character. The findings indicate that worship and moral education provided by parents from an early age form a fundamental basis for creating devout and morally upright Muslim generations. The conclusion drawn is that the role of parents in educating their children in line with Islamic teachings significantly influences the child's future, both in this world and the hereafter.